Rapid Identification and Multiple Susceptibility Testing of Pathogens from Positive-Culture Sterile Body Fluids by a Combined MALDI-TOF Mass Spectrometry and Vitek Susceptibility System - Tian, Yueru; Zheng, Bing; Wang, Bei; Lin, Yong; Li, Min (Frontiers in Microbiology, 2016)
Infections of the bloodstream, central nervous system, peritoneum, joints and other sterile areas are associated with high morbidity and sequelae risk. Timely initiation of effective antimicrobial therapy is crucial to improving patient prognosis. However, standard final identification and antimicrobial susceptibility tests (ASTs) are reported 16–48 hours after a positive alert. For a rapid, effective and low-cost diagnosis, we combined matrix-assisted laser desorption/ionization time of flight mass spectrometry with a Vitek AST system, and performed rapid microbial identification (RMI) and rapid multiple AST (RMAST) on non-duplicated positive body fluid cultures collected from a hospital in Shanghai, China. Sterile body fluid positive culture and blood positive culture caused by Gram negative (GN) or polymicrobial were applied to the MALDI–TOF measurement directly. When positive blood culture caused by Gram positive (GP) bacteria or yeasts, they were resuspended in 1 ml brain heart infusion for 2h or 4h enrichment, respectively. Regardless of enrichment, the RMI (completed in 40 min per sample) accurately identified GN and GP bacteria (98.9% and 87.2%, respectively), fungi (75.7%) and anaerobes (94.7%). Dominant species in multiple cultures and bacteria that failed to grow on the routing plates were correctly identified in 81.2% and 100% of cases, respectively. The category agreements of RMAST results, determined in the presence of various antibiotics, were similarly to previous studies. The RMI and RMAST results not only reduce the turnaround time of the patient report by 18–36 hours, but also indicate whether a patient’s antibiotic treatment should be accelerated, ceased or de-escalated, and adjusted the essential drugs modification for an optimised therapy.